2014
DOI: 10.1128/mbio.01909-14
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Herpesvirus Capsid Motility Is Not Dependent on F-Actin

Abstract: A considerable part of the herpesvirus life cycle takes place in the host nucleus. While much progress has been made to understand the molecular processes required for virus replication in the nucleus, much less is known about the temporal and spatial dynamics of these events. Previous studies have suggested that nuclear capsid motility is directed and dependent on actin filaments (F-actin), possibly using a myosin-based, ATP-dependent mechanism. However, the conclusions from these studies were indirect. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…Phalloidin staining in fixed cells gave the same results. 12 We could only detect nuclear F-actin structures in infected superior cervical ganglion (SCG) neurons using Phalloidin as reported earlier, but not with Lifeact. We were therefore unable to directly visualize if nuclear F-actin structures support capsid motility because i) all cell types tested with the exception of primary cultures of SCG neurons did not induce detectable nuclear F-actin ii) Nuclear F-actin in SCG neurons could only be detected after fixation and staining with fluorescent phalloidin.…”
Section: Nuclear Capsid Motility Is Not Dependent On F-actinmentioning
confidence: 59%
“…Phalloidin staining in fixed cells gave the same results. 12 We could only detect nuclear F-actin structures in infected superior cervical ganglion (SCG) neurons using Phalloidin as reported earlier, but not with Lifeact. We were therefore unable to directly visualize if nuclear F-actin structures support capsid motility because i) all cell types tested with the exception of primary cultures of SCG neurons did not induce detectable nuclear F-actin ii) Nuclear F-actin in SCG neurons could only be detected after fixation and staining with fluorescent phalloidin.…”
Section: Nuclear Capsid Motility Is Not Dependent On F-actinmentioning
confidence: 59%
“…However, further study of this hypothesis has been missing for more than a decade. We recently reinvestigated this idea, and did not find any evidence that herpesviruses induce nuclear F-actin (10).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we and others provided data that suggested that herpesvirus capsids use an active, directed mechanism based on F-actin to transport through the nucleoplasm (8,9) and/or that nuclear F-actin is involved in capsid assembly. However, we recently showed that herpesviruses do not induce nuclear F-actin in most cells, and, more importantly, that nuclear capsid motility is not dependent on nuclear F-actin (10). This led us to reinvestigate nuclear capsid motility by single particle tracking to address whether molecular motors power it.…”
mentioning
confidence: 99%
“…The herpesvirus particle is composed of a capsid containing the double-stranded DNA genome, which is surrounded by a tegument layer and an envelope containing viral glycoproteins (1). During the herpesvirus life cycle, genome synthesis, capsid assembly, DNA incorporation (2), and primary tegumentation (3) occur in the nuclei of infected cells. Subsequently, nucleocapsids leave the nucleus by budding through the nuclear membrane via an envelopment-de-envelopment pathway (4,5).…”
mentioning
confidence: 99%